Engineering herbicide resistance in plants by expression of a detoxifying enzyme - Block, M. De (1987)
Phosphinothricin (PPT) is a potent inhibitor of glutamine synthetase in plants and is used as a non-selective herbicide. The bar gene which confers resistance in Streptomyces hygroscopicus to bialaphos, a tripeptide containing PPT, encodes a phosphinothricin acetyltransferase (PAT) (see accompanying paper). The bar gene was placed under control of the 35S promoter of the cauliflower mosaic virus and transferred to plant cells using Agrobacterium-mediated transformation. PAT was used as a selectable marker in protoplast co-cultivation. The chimeric bar gene was expressed in tobacco, potato and tomato plants. Transgenic plants showed complete resistance towards high doses of the commercial formulations of phosphinothricin and bialaphos. These data present a successful approach to obtain herbicide-resistant plants by detoxification of the herbicide.